Measuring The Competitiveness Of Malaysian Tourism Cities Through The Application Of Multi Dimensional Scaling Analysis. - Mohamed, Badaruddin; omar, Shida irwana; Muhibudin, Masitah; Shamsuddin, Nurhashikin (2009)
Tourist destinations contain many desired or expected attributes by travelers. At the same time, the image of a destination has been identified as an influence factor of tourist's travel decision-making, cognition and behaviour at a destination.